x+3y=6 ----------------------------(1)
2x+4y=12---------------------------(2)
Using elimination method to solve;
we will eliminate x variable
To do that, we must make sure the coefficient of x in the two equation are the same.
This can be achieved by multiplying equation (1) by 2 and equation (2) by 1
That is;
2x + 6y = 12 ----------------------(3)
2x + 4y = 12 -----------------------(4)
subtract equation (4) from equation (3)
2y = 0
Divide both-side of the equation by 2
y=0
substitute y = 0 into equation (1)
x + 3(0) = 6
x = 6